2015
DOI: 10.1038/srep07919
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity and Anti-Hyperglycemic Effects of Cinnamaldehyde via altered Ghrelin Secretion and Functional impact on Food Intake and Gastric Emptying

Abstract: Cinnamon extract is associated to different health benefits but the active ingredients or pathways are unknown. Cinnamaldehyde (CIN) imparts the characteristic flavor to cinnamon and is known to be the main agonist of transient receptor potential-ankyrin receptor 1 (TRPA1). Here, expression of TRPA1 in epithelial mouse stomach cells is described. After receiving a single-dose of CIN, mice significantly reduce cumulative food intake and gastric emptying rates. Co-localization of TRPA1 and ghrelin in enteroendoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
131
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(139 citation statements)
references
References 40 publications
7
131
1
Order By: Relevance
“…5). Previous studies have shown that long-term CA supplementation in food can protect mice from diet-induced obesity and hyperglycemia [3, 7]. In vitro , upon chronic treatment with CA, Fgf21 and Ucp1 were significantly upregulated in both murine inguinal adipocytes and human subcutaneous fat cultures (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…5). Previous studies have shown that long-term CA supplementation in food can protect mice from diet-induced obesity and hyperglycemia [3, 7]. In vitro , upon chronic treatment with CA, Fgf21 and Ucp1 were significantly upregulated in both murine inguinal adipocytes and human subcutaneous fat cultures (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 88%
“…While the beneficial effects of CA on systemic metabolism have recently been observed [3, 4, 7], the underlying molecular basis of these effects remains largely unknown. To explore the possibility that CA influences whole body metabolism through direct action on adipocytes, we treated fully differentiated adipocytes isolated from the murine inguinal subcutaneous fat depot with CA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 These findings suggest the potential relevance of icilin and 'icilin-like' compounds as therapeutic strategy for the treatment of a variety of pathological conditions. Although Wei 13 and Foster, et al 14 made some further investigations into variations of the icilin structure, they did not report either the potency of their compounds (EC 50 ) or their selectivity.…”
mentioning
confidence: 98%
“…Some compounds (compounds 11) with a contracted central ring were prepared by a modification of this approach 16 (Scheme 2). The rigid analogs, 16, were prepared by the original pathway utilizing tetralone (12) or 5-nitro-or 7-nitro-tetralone (13) as the starting material 17 (Scheme 3).…”
mentioning
confidence: 99%